2018
DOI: 10.1097/psy.0000000000000550
|View full text |Cite
|
Sign up to set email alerts
|

Time of Day When Type 1 Diabetes Patients With Eating Disorder Symptoms Most Commonly Restrict Insulin

Abstract: Findings suggest that insulin restriction may be less likely in the morning, and that late afternoon is a potentially important time for additional therapeutic support. Results also suggest that systematic clinical assessment and treatment of overnight eating might improve T1D management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 13 publications
0
21
0
4
Order By: Relevance
“…The recruitment target was N = 25, for a final sample of N = 21 with attrition. Assuming two-tailed α = .05, a pre-post mean of average 3-day blood glucose correlation of 0.7, and SD = 58.08 mg/dL (calculated from prior data [ 17 , 31 ], a sample size of 21 provided 80% power to detect a reduction of at least 32 mg/dL in average daily blood glucose, equivalent to a .5% reduction in HbA 1c , which is considered clinically significant [ 36 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The recruitment target was N = 25, for a final sample of N = 21 with attrition. Assuming two-tailed α = .05, a pre-post mean of average 3-day blood glucose correlation of 0.7, and SD = 58.08 mg/dL (calculated from prior data [ 17 , 31 ], a sample size of 21 provided 80% power to detect a reduction of at least 32 mg/dL in average daily blood glucose, equivalent to a .5% reduction in HbA 1c , which is considered clinically significant [ 36 ].…”
Section: Methodsmentioning
confidence: 99%
“…These settings have the advantage of providing therapeutic support in the moment that individuals are making decisions about their T1D management. A mobile app can similarly provide additional therapeutic support anytime, including in the late afternoon or overnight when individuals may be more prone to skip insulin [ 31 ]. The app was also included to expedite skill acquisition and generalization to daily life (a common obstacle in cognitive behavioral therapy) [ 32 ] and it allowed T1D patients to track daily behavior change goals, rather than relying on distal outcomes, such as HbA 1c .…”
Section: Introductionmentioning
confidence: 99%
“…Previous continuous glucose monitoring (CGM)based studies in type 1 diabetes and disordered eating have shown that insulin omission/restriction is associated with higher post-meal glucose. [17][18][19] Thus, people with disordered eating may experience greater fluctuation in their glucose, which is not reflected in their HbA 1c . This study aimed to characterise glycaemia of people with type 1 diabetes and disordered eating and explore association of these glycaemic changes with emotion and diabetes self-care behaviours.…”
Section: Introductionmentioning
confidence: 99%
“…Gece ara öğünü için belirlenen net bir zamanın olmayışı, bu konudaki önerileri de karmaşık hale getirmektedir. Genel olarak ana öğünden 2.5-3 saat sonrası ara öğünün başlangıcı olarak kabul edilmektedir (5). Bolus insülin verilmeden tüketilen atıştırmalıklar ve sık ara öğün almak ise glukoz profilinde bozulmaya neden olmaktadır (1,6,7).…”
Section: Introductionunclassified